Effects of Total Flavonoids of Epimedium on Bone Marrow Adipose Tissue in Ovariectomized Rats - Chen, Lei; Ma, Rui; Luo, Peng; Shi, Dan; Shi, Xiao; Nian, Hua; Chang, Shi-Xin; Yuan, Wei; Li, Guan-Wu (Frontiers in Endocrinology, 2022)
Bone marrow adipose tissue has brown fat characteristics. Several studies have demonstrated that total flavonoids of Epimedium (TFE) could prevent bone loss and reduce the white adiposity in bone marrow induced by ovariectomy (OVX) in rats. However, the effects of TFE on marrow brown fat in OVX rats remain unclear. In this word, we addressed this question expected to provide a new target for preventing and treating osteoporosis. Thirty-six 3-month-old female Sprague-Dawley rats were equally divided into Sham controls, OVX controls, and OVX treated with TFE. Chemical shift coding magnetic resonance was performed to detect marrow fat fraction at the left femur at baseline, 6 and 12 weeks post-OVX. Bone mineral density at the lumbar spine and femur was measured by dual-energy x-ray absorptiometry. Serum bone biomarkers by ELISA, trabecular bone microarchitecture at the proximal tibia by micro-CT, quantitative parameters of marrow adipocyte by hematoxylin, and eosin staining were evaluated. The marrow adipocyte gene and protein expressions profile were determined by real-time quantitative PCR and immunostaining in whole tibiae. We found that TFE treatment could decrease bone turnover rate and improved bone mineral density and trabecular microarchitecture in OVX rats. OVX resulted in marrow adipogenesis as evidenced by increased marrow fat fraction, larger marrow adipocyte size, increased adipocyte number and percentage of adipocyte area, marrow white adipocyte gene, and protein expression, including PPAR2 and FABP4. These pathological changes induced by estrogen deficiency were restored by TFE treatment. TFE also increased brown adipocyte expressions of the transcription factor Ucp1 and Prdm16 in whole tibiae. There was no detectible protein expression of brown adipocyte markers in the proximal tibia. Taken together, TFE regulation of bone marrow adiposity in OVX rats is mediated, at least in part, via maintaining the reciprocity of white and brown adipose tissue.